Overlapping Authority to Make Land Deeds in Indonesia (A critical review of the realisation of legal order) - Ananda, Heppy Trio; Permadi, Iwan; Supriyadi, Supriyadi (Institut Agama Islam Negeri Curup, 2024)
The concurrent authority of Notaries and Land Deed Officials (PPATs) in creating land deeds in Indonesia has resulted in legal ambiguity. This research employs a normative juridical approach, scrutinizing existing legal norms to ascertain the extent of authority granted to Notaries and PPATs and to identify potential conflicts. The findings indicate that the Notary Position Law (Law No. 30/2004, amended by Law No. 2/2014) endows Notaries with extensive authority, implying they are not confined by the restrictions in Government Regulation No. 24/2016. The existing ambiguity calls for legislative clarification. The study concludes that Notaries possess broad authority to draft land deeds, mostly unaffected by limitations on PPATs. Legislative measures are required to delineate clearer jurisdictional boundaries, ensuring legal certainty and preventing potential abuses of power. This research examines the realization of legal order in the context of overlapping authority to make land deeds in Indonesia.